The Influence of Customer Service on Customer Satisfaction (Case Study in Bank BJB Cash Office Yantap Garut) - Adryan Septiady; Diana Nurwulandari (PT Inovasi Pratama Internasional, 2022)
Satisfaction is a person’s feeling after comparing the perceived performance results with what he expects, factors that can affect customer satisfaction, one of which is the service provided by customer service to its customers. This study aims to analyze the effect of customer service on customer satisfaction at Bank BJB Kantor Kas Yantap Garut. The research method uses descriptive and associative methods with a quantitative approach. The population of this research is customers who have attachments and linkages with customer service Bank BJB Kantor Kas Yantap Garut. Determination of the sample based on the opinion of Indrawan and Yaniawati (2014:103) so that the sample of this study was 68 respondents using non-probability sampling technique with incidental sampling. The results of data processing obtained from the Spearman rank correlation test showed that customer service has a strong influence on customer satisfaction with a value of 0,722 and a coefficient of determination of 0,52 or 52%, and the remaining 48% is influenced by other factors not examined in this study. Based on the results of the study (8,518) > t-table (1,997) indicates that customer service has a positive and significant effect on customer satisfaction.